2008
DOI: 10.1111/j.1467-9361.2008.00475.x
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium Exchange Rates in New EU Members: External Imbalances versus Real Convergence

Abstract: In new EU members, the accumulation of net foreign liabilities has gone hand-in-hand with real exchange rate appreciations, contrary to intuition. This may be due to the induced effect that capital inflows on productivity and competitiveness (Balassa-Samuelson effect). An extended empirical model comprising relative productivity and net foreign assets is well-suited to capture this indirect, opposite effect of liabilities accumulation on the equilibrium exchange rates for the three largest economies: Poland, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…For example, Refs. [119,120,136] theoretically showed that an increase in NFA does not necessarily lead to the appreciation of the national currency.…”
Section: Appendix B Conceptual Framework For Modeling the Saudi Reermentioning
confidence: 99%
See 3 more Smart Citations
“…For example, Refs. [119,120,136] theoretically showed that an increase in NFA does not necessarily lead to the appreciation of the national currency.…”
Section: Appendix B Conceptual Framework For Modeling the Saudi Reermentioning
confidence: 99%
“…The authors of [136,137] discussed the failure of traditional theoretical models of the real exchange rates, such as the portfolio balance approach. They developed a theoretical model in which the sign of the NFA coefficient in the real exchange rate equation is not necessarily positive.…”
Section: Appendix B Conceptual Framework For Modeling the Saudi Reermentioning
confidence: 99%
See 2 more Smart Citations
“…Southern and peripheral states have run a large number of deficits due to overvalued currency misalignments as shown by Coudert et al (2013), Couharde and Mazier (2001), Alberola and Navia (2008) and others. But estimating an equilibrium exchange rate to avoid divergent rates is complicated by the structural change experience at the transition phase as Maeso-Fernandez et al (2006) claims, and by the larger inflation differentials as Honohan and Lane (1999) argue.…”
Section: Introductionmentioning
confidence: 99%